Takotsubo cardiomyopathy complicating acute on chronic pancreatitis: A case report - Rajan, Swaminathan; Amarapathi, Sivasankar; Durairaj, Somasekar (Asian Journal of Medical Sciences, 2023)
Acute or chronic pancreatitis as a trigger of Takotsubo cardiomyopathy (TCM) has been infrequently described in the literature. Misdiagnosis of this phenomenon can often occur due to overlap in symptomology, particularly in those outside of the usual. A 50-year-old man with a history of alcohol abuse presented with epigastric and chest pain. Electrocardiography showed ischemic changes, and laboratory workup revealed elevated lipase, amylase, and troponin. He was diagnosed with acute pancreatitis and managed presumptively as acute coronary syndrome, class 4 angina. Patient had no signs of chronic liver disease, his pulmomary system was stable. He was a known case of left upper limb thrombosis and had portal venous thrombosis and was on tablet Rivaraxoban 10 mg. Subsequent coronary angiography was negative for obstructive coronary artery disease, and left ventriculography demonstrated basal hyperkinesis and apical akinesis, characteristic of TCM. TCM is a rare complication of acute pancreatitis. Increased awareness of this phenomenon is required to prevent delays in diagnosis and avoid unnecessary interventions and complications.